Multipartite entanglement criterion via generalized local uncertainty relations - Jia-Bin Zhang (Nature Portfolio, 2021)
Abstract We study the detection of multipartite entanglement based on the generalized local uncertainty relations. A sufficient criterion for the entanglement of four-partite quantum systems is presented in terms of the local uncertainty relations. Detailed examples are given to illustrate the advantages of our criterion. The approach is generalized to general multipartite entanglement cases.